2016
DOI: 10.1093/sysbio/syw002
|View full text |Cite
|
Sign up to set email alerts
|

Rarity and Incomplete Sampling in DNA-Based Species Delimitation

Abstract: DNA-based species delimitation may be compromised by limited sampling effort and species rarity, including "singleton" representatives of species, which hampers estimates of intra- versus interspecies evolutionary processes. In a case study of southern African chafers (beetles in the family Scarabaeidae), many species and subclades were poorly represented and 48.5% of species were singletons. Using cox1 sequences from >500 specimens and ∼100 species, the Generalized Mixed Yule Coalescent (GMYC) analysis as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 67 publications
5
153
1
Order By: Relevance
“…In the case of GMYC and PTP, our findings corroborate the study of Ahrens et al. () highlighting that rarely sampled species are not problematic per se for tree‐based approaches to species delimitation. The impact of sampling pattern was most dramatic for haplowebs: this is because the sampling of only two sequences per species is equivalent to sampling a single diploid individual, the two haplotypes of which are automatically considered conspecific using the haploweb approach (unlike tree‐based or distance‐based approaches that may consider them as heterospecific).…”
Section: Resultssupporting
confidence: 89%
“…In the case of GMYC and PTP, our findings corroborate the study of Ahrens et al. () highlighting that rarely sampled species are not problematic per se for tree‐based approaches to species delimitation. The impact of sampling pattern was most dramatic for haplowebs: this is because the sampling of only two sequences per species is equivalent to sampling a single diploid individual, the two haplotypes of which are automatically considered conspecific using the haploweb approach (unlike tree‐based or distance‐based approaches that may consider them as heterospecific).…”
Section: Resultssupporting
confidence: 89%
“…This matches the result of a recent simulation study showing that single‐locus tree‐based, distance‐based and allele sharing‐based approaches give congruent species hypotheses when dealing with highly variable markers in species of small effective population size and low speciation rate (Dellicour and Flot ). Yet, several studies found that the ability of MMs to delimit species accurately declined as the mean or among‐species variance in effective population size (Ne) increased (Esselstyn et al , Fujisawa and Barraclough , Dellicour and Flot , Ahrens et al ). However, larger Ne was either found to result in over‐splitting or lumping depending on the method used, differences in Ne between the common ancestor and descendant species and most importantly on the relative change of speciation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Congruence of morphological species units with mOTUs was quantified with the match ratio adapted from Ahrens et al. (); the match ratio is calculated as follows: 2 × N match /( N mOTU + N morph ), where N match is the number of putative species that are the same between the two methods of delimitation, and N mOTU and N morph refer to the total number of mOTUs at a given percentage distance threshold and total number of morphological species units, respectively.…”
Section: Methodsmentioning
confidence: 99%